Prevalence of key resistance alleles associated with DMI and SDHI fungicide resistance in European Zymoseptoria tritici populations in 2022 - S. Kildea; T. Heick; F. Hutton; C. Bataille; L. Aldén; J. Kaneps; A. Mäe; S. Weigand; J. Zajc; A. S. Walker; P. Hellin (Journal of Plant Diseases and Protection, 2025)

Allocating catches to species in mixed species data – A model-based approach - D. Parker; A.E. Punt; R.A. Deng; W.N. Venables; C.M. Dichmont; A.G. Donovan; R.A. Kenyon; T. van der Velde; M. Miller; T. Hutton (Fisheries Research, 2025)

Characterization of sites of scientific interest for ESA's PROSPECT instrument - S.J. Boazman; D. Heather; M. Hutton; M. Schwinning; A. Frigeri; N. Schmitz; S. Besse; M. Formisano; C. De Sanctis; C. Gscheidle; C. Orgel; P. Reiss; et al. (Icarus, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Objective and Subjective Measurements of Freshmen and Sophomore’s Fruit and Vegetable Intake - T. Ibiyemi; W. Najam; A. Sosa; S. Makerecha; T. Hutton; S. Bryant; W. Oldewage-Theron (Journal of the Academy of Nutrition and Dietetics, 2023)

Effect of planning policies on land use dynamics and livelihood opportunities under global environmental change: Evidence from the Mekong Delta - Tristan Berchoux; Craig W. Hutton; Oliver Hensengerth; Hal E. Voepel; Van P.D. Tri; Pham T. Vu; Nghia N. Hung; Dan Parsons; Stephen E. Darby (Land Use Policy, 2023)

125 Quantification of chewing frequency in horses consuming bermudagrass hay compared with other popular equine forages - J. Farmer; T. Callaway; J. Duberstein; K. Duberstein; R. Hutton (Journal of Equine Veterinary Science, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Impact of various lipophilic substituents on ruthenium(II), rhodium(III) and iridium(III) salicylaldimine-based complexes: synthesis, in vitro cytotoxicity studies and DNA interactions - Irwin Cassells; Tameryn Stringer; Alan T. Hutton; Sharon Prince; Gregory S. Smith (JBIC Journal of Biological Inorganic Chemistry, 2018)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Detection of infectious bronchitis virus 793B, avian metapneumovirus, Mycoplasma gallisepticum and Mycoplasma synoviae in poultry in Ethiopia - S. Hutton; J. Bettridge; R. Christley; T. Habte; K. Ganapathy (Tropical Animal Health and Production, 2017)

Trade‐offs in transitions between indigenous and commercial fishing sectors: the Torres Strait tropical rock lobster fishery - T. Hutton; E.I. van Putten; S.D. Pascoe; R.A. Deng; É.E. Plagányi; D. Dennis (Fisheries Management and Ecology, 2016)
A bio‐economic model was developed to evaluate aspects of proposed quota‐based constraints vs the current effort control regulations for the tropical rock lobster, Panulirus ornatus, Fabricius, fishery in the Torres Strait (Australia/Papua New Guinea). The analysis integrates across biological, economic and social considerations. Model performance indicators have been chosen to reflect higher level policy objectives. The model simulation results indicate important trade‐offs. There is lower overall fleet total profit (across all the subfleets), lower fishery total value added and lower total employment if the fishery is quota‐constrained. This is due to an assumed rationalisation driven by incentives and current utilisation of capacity. The simulated re‐allocation of quota from the commercial non‐indigenous fleet allowing for greater potential indigenous fisher participation results in predicted increases in indigenous employment and would meet social objectives; however, due to limited capacity in the indigenous fleet, the simulated predicted lower catches led to lower total fishery profits and decreased total fishery value added within the supply chain. Investment in capacity could potentially offset this result.

Multispecies fisheries management and conservation: tactical applications using models of intermediate complexity - Éva E Plagányi; André E Punt; Richard Hillary; Elisabetta B Morello; Olivier Thébaud; Trevor Hutton; Richard D Pillans; James T Thorson; Elizabeth A Fulton; Anthony D M Smith; Franz Smith; Peter Bayliss; et al. (Fish and Fisheries, 2014)
Stakeholders increasingly expect ecosystem assessments as part of advice on fisheries management. Quantitative models to support fisheries decision‐making may be either strategic (‘big picture’, direction‐setting and contextual) or tactical (focused on management actions on short timescales), with some strategic models informing the development of tactical models. We describe and review ‘ M odels of I ntermediate C omplexity for E cosystem assessments’ ( MICE ) that have a tactical focus, including use as ecosystem assessment tools. MICE are context‐ and question‐driven and limit complexity by restricting the focus to those components of the ecosystem needed to address the main effects of the management question under consideration. Stakeholder participation and dialogue is an integral part of this process. MICE estimate parameters through fitting to data, use statistical diagnostic tools to evaluate model performance and account for a broad range of uncertainties. These models therefore address many of the impediments to greater use of ecosystem models in strategic and particularly tactical decision‐making for marine resource management and conservation. MICE are capable of producing outputs that could be used for tactical decision‐making, but our summary of existing models suggests this has not occurred in any meaningful way to date. We use a model of the pelagic ecosystem in the C oral S ea and a linked catchment and ocean model of the G ulf of C arpentaria, A ustralia, to illustrate how MICE can be constructed. We summarize the major advantages of the approach, indicate opportunities for the development of further applications and identify the major challenges to broad adoption of the approach.

The quandary of quota management in the T orres S trait rock lobster fishery - I. van Putten; R. Deng; D. Dennis; T. Hutton; S. Pascoe; E. Plagányi; T. Skewes (Fisheries Management and Ecology, 2013)
Islanders, commercial non‐indigenous fishers and P apua N ew G uinea fishers share the tropical rock lobster fishery, P anulirus ornatus ( F abricius) in T orres S trait. As the fishery is in the process of moving from input to output controls, a pre‐implementation understanding of indigenous fishers' perceptions of the potential impact of different quota management systems is gained. This study, based on workshops and interviews, considers the impact of competitive quota, community quota and a hybrid system with individually tradeable quota ( ITQ ), and broadens the current biological focus of fisheries management through consideration of economic, social and cultural aspects. The perceived quota system impact on indigenous lobster fishers largely mirrors the experience internationally, with unlimited access and self‐determination considered most important. The heterogeneity of the indigenous sector increases the management complexity for this fishery, but needs to be taken into consideration if unexpected consequences of the chosen quota management system are to be avoided.

Conservation genetics and ecology of an endemic montane palm on Lord Howe Island and its potential for resilience - A. Shapcott; I. Hutton; W. J. Baker; T. D. Auld (Conservation Genetics, 2012)

How sympatric is speciation in the Howea palms of Lord Howe Island? - WIESŁAW BABIK; ROGER K. BUTLIN; WILLIAM J. BAKER; ALEXANDER S. T. PAPADOPULOS; MATTHIEU BOULESTEIX; MARIE‐CHARLOTTE ANSTETT; CHRISTIAN LEXER; IAN HUTTON; VINCENT SAVOLAINEN (Molecular Ecology, 2009)
The two species of the palm genus Howea (Arecaceae) from Lord Howe Island, a minute volcanic island in the Tasman Sea, are now regarded as one of the most compelling examples of sympatric speciation, although this view is still disputed by some authors. Population genetic and ecological data are necessary to provide a more coherent and comprehensive understanding of this emerging model system. Here, we analyse data on abundance, juvenile recruitment, pollination mode and genetic variation and structure in both species. We find that Howea forsteriana is less abundant than Howea belmoreana . The genetic data based on amplified fragment length polymorphisms markers indicate similar levels of variation in the two species, despite the estimated census population size of H. belmoreana being three times larger than that of H. forsteriana . Genetic structure within species is low although some weak isolation by distance is detectable. Gene flow between species appears to be extremely limited and restricted to early‐generation hybrids – only three admixed individuals, classified as F2s or first generation backcrosses to a parental species, were found among sampled palms. We conclude that speciation in Howea was indeed sympatric, although under certain strict definitions it may be called parapatric.

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Short and long term effects of antipsychotic medication on smooth pursuit eye tracking in schizophrenia - S. Hutton; T. Crawford; H. Gibbins; I. Cuthbert; T. Barnes; C. Kennard; E. Joyce (Psychopharmacology, 2001)